The Chinese in Cuba, 1847-Now - García Triana, Mauro; Eng Herrera, Pedro (Lexington Books, 2009)
This book deals with Chinese immigrants' role in the struggle for Cuban liberation and in Cuba's twentieth-century revolutionary social movement; the history of the Chinese economy in Cuba; and the Chinese contribution to Cuban music, painting, food, sport, and language. The centerpiece of the book is a translation of a study by Mauro Garc'a Triana and Pedro Eng Herrera on the history of the Chinese presence in Cuba. Over many years, Garc'a and Eng have collaborated closely on scholarly research on the Chinese contribution to Cuban life and politics, although their work is not widely known. Both are well equipped for such an enterprise: Eng as a Cuban of Chinese descent and a participant in the ethnic-Chinese revolutionary movement in Cuba, starting in the 1950s; Garc'a as a participant in the struggle against Batista and Cuban Ambassador to China during the period of the Cultural Revolution. The study is supplemented by an extensive collection of archival photographs and of paintings on Cuban-Chinese themes by Pedro Eng, who is not just a chronicler of the community but a well-known worker-artist who paints in a style described by commentators as 'naive.' The volume has three appendices: excerpts from the Cuba Commission's 1877 report on Chinese emigration to Cuba; the rebel leader Gonzalo de Quesada y Ar-stegui's pamphlet 'The Chinese and Cuban Independence,' translated from his book Mi primera ofrenda (My first offering), first published in 1892; and the chapter on 'Coolie Life in Cuba' from Duvon Clough Corbitt's Study of the Chinese in Cuba, 1847-1947 (Wilmore 1971).